Traditional ecological knowledge and its role in biodiversity conservation: a systematic review - Sinthumule, Ndidzulafhi I. (Frontiers in Environmental Science, 2023)
In various parts of Africa, scholars have paid a great deal of attention to TEK, focusing mainly on their role in biodiversity conservation or natural resource management. Despite individual efforts made so far, the consolidated information about the role of TEK in biodiversity conservation remains uncertain in Africa. A systematic literature search on the role of TEK in biodiversity conservation was conducted on ISI Web of Science (WoS), Scopus and Google Scholar databases. The search produced 40 papers in 12 countries in Africa that were published between 2001 and 2022. Majority of studies on TEK (40%; n = 16) reported in the reviewed literature were from West Africa and no study was found in North Africa. The study found the regular use of different but interrelated forms of TEK in Africa. These include taboos and totems, customs and rituals, rules and regulations, metaphors and proverbs, traditional protected areas (social institutions), local knowledge of plants, animals and landscapes, and resource management systems. Although these forms of TEK have great potential for in situ natural resource management, metaphors and proverbs were found to be least addressed (n = 4) component of TEK. Despite TEK having played a significant role in biodiversity conservation in present-day Africa, the traditions are being threatened by changing cultural mores and practices (including Christianity and Islam), formal education, modernisation and new political dispensations. The findings of this study demonstrate that large geographic areas remain unexplored and this may hide part of the narrative. Reviewed literature suggests that metaphors and proverbs are least represented. New studies should be dedicated towards filling these gaps. Based on these findings, recommendations are provided to improve management practices for TEK in Africa.